Kurikulum Pendidikan Islam: Hakikat, Prinsip, dan Orientasi Nilai - Syahrendi Wardana, Putra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Agama Islam Miftahul Ula (STAIM) Kabupaten Nganjuk, Indonesia., 2025)
Curriculum serves as a fundamental tool to achieve educational objectives. In the context of Islamic education, it is not merely a compilation of subjects but a structured framework grounded in divine sources namely, the Qur’an and Hadith. The Islamic education curriculum must be clearly designed and systematically formulated to convey a coherent body of knowledge from educators to learners. It also encompasses educational processes that shape students’ intellectual, moral, and spiritual development. The curriculum should be developed based on ontological, epistemological, and axiological foundations rooted in Islamic thought. This study employs a qualitative approach using a library research method and content analysis. The data are drawn from various scholarly sources and analyzed through theoretical and philosophical perspectives to examine the essence, principles, and value orientation of the Islamic education curriculum. This methodological framework allows for a comprehensive exploration of how Islamic principles shape curriculum design. The findings reveal that the Islamic education curriculum is distinguished by several foundational principles: it is based on Islamic values, directed toward achieving educational goals, integrative across disciplines, relevant, flexible, efficient, continuous, individualized, and equitable. Furthermore, it emphasizes the preservation and internalization of Islamic values in students. Education, understood as a conscious effort to humanize individuals, relies heavily on curriculum as a guiding instrument. Therefore, the Islamic education curriculum must align with the holistic vision of Islam, ensuring the development of learners who are intellectually competent and spiritually grounded.